Rancang Bangun Aplikasi Pemeliharaan Ikan Koi Berbasis Android dengan Menggunakan Teknologi IoT - Raehan Widi Sugiarto; Muhammad Zakariyah (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) AMIK Indonesia, 2024)
In the maintenance of Koi fish, the quality of the pond environment and water plays an important role in the success of Koi fish care. Koi fish or commonly known by another name Cyprinus Rubrofuscus is one type of freshwater ornamental fish that is very sensitive to pond environmental conditions and water quality. At this time many people want to keep koi fish as pets or even make koi fish as a business. Koi fish is one of the difficult fish to maintain because it requires extra monitoring of the pond conditions and water conditions of the koi fish pond. The difficulty of monitoring pond conditions and water conditions in koi fish ponds presents an idea to develop an Android-based Koi Fish Monitoring and Maintenance application using IoT technology in its design. The existence of this application aims to analyze the application of Internet of Things (IoT) technology to help the maintenance and care of koi fish. By using the IoT technology study method to monitor the condition of koi fish care automatically, it is hoped that this application can be able to facilitate accurate monitoring of pond and water conditions.